On the plyometric nature of Olympic weightlifting biomechanical considerations for practical applications in strength and conditioning for sport - Squillante, A. (European Journal of Physical Education and Sport Science, 2018)
Olympic-style weightlifting exercises have found their place in the training of speed and power athletes. A systematic review of the most accredited academic literature provides kinetic and kinematic data to define the relationship between change in vertical ground reaction force (GRF), peak vertical bar velocity, average joint angular displacement and average joint angular velocity during the snatch, clean and jerk. Important similarities between jumping mechanics - the paradigm of power development in sport - and the pull in Olympic weightlifting have provided insight on the plyometric nature of these explosive movements, supporting the use of full lifts - snatch, clean and jerk - in the training of elite level athletes.